Neutralizing antibody landscape of the non-polio Enteroviruses and future strategy - Wang, Hongye; Zhu, Wenbing; Li, Ya; Sun, Ming (Frontiers in Immunology, 2025)
The non-polio Enteroviruses (NPEVs), consist of enteroviruses, coxsackieviruses, echoviruses, and rhinoviruses, are causative agents for a wide variety of diseases, ranging from common cold to encephalitis and acute flaccid paralysis (AFP). In recent years, several NPEVs have become serious public health threats, include EV-A71, which has caused epidemics of hand-foot-and-mouth disease (HMFD) in Southeast Asia, and EV-D68, which caused outbreaks of severe respiratory disease in children worldwide. Infections with these viruses are associated with neurological diseases like aseptic meningitis and AFP. Currently, apart from inactivated EV-A71 vaccines that were developed in China, no effective measures are available to prevent or treat NPEV infections. Antibody-mediated immunity is crucial for preventing and limiting viral infections, and potent neutralizing antibodies could serve as potential therapeutic agents. In this review, we describe recent progress in the NPEVs neutralization antibodies, summarizing the characteristics, breadth, and potency against NPEVs, such as EV-A71, CVA16, EV-D68, and echovirus. We focus on not only through the study of viral epitopes but also through the understanding of virus-antibody interactions. Also, we decipher the role of antibodies in the attachment of the virus to receptors, internalization, and uncoating process, providing insight into virus neutralization mechanisms. Moreover, bi-specific antibodies or multivalent antibodies with better potency are also discussed. Therefore, an in-depth understanding of structures of enterovirus and mechanisms of antibody neutralization should be useful for future strategies in guiding the design of a rational antiviral agent against NPEVs infections.